2013
DOI: 10.1155/2013/594561
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Use of Probiotic-Containing Yogurts Is a Safe Way to PreventHelicobacter pylori: Based on a Mongolian Gerbil's Model

Abstract: Background. The suppression of Helicobacter pylori (H. pylori) decreases H. pylori-related diseases. The probiotics have an inhibitory effect on H. pylori. Aim. We investigated the effects of long-term use of yogurt on H. pylori based on Mongolian gerbils' model. Materials and Methods. Yogurt (containing a supplement of Lactobacillus acidophilus, Bifidobacterium lactis, etc.) was used. Forty-six gerbils were divided into five groups. All groups were inoculated with H. pylori for 5 to 8 weeks. The yogurt was gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 40 publications
(33 reference statements)
2
4
0
Order By: Relevance
“…For example, several Gram-positive probiotic can synthesize antimicrobial peptides, acetic, lactic, and propionic acid which reduce the intestinal pH and consequently inhibit the growth of several pathogenic Gram-negative bacteria [ 87 ]. These data were further supported by several other studies [ 88 90 ] which showed that several strains of lactobacilli have antagonistic activities against Gram-negative gastric-cancer-related Helicobacter pylori . Furthermore, another study found that some Lactobacillus strains produce lactic acid which inhibits the growth of Salmonella enterica [ 91 ].…”
Section: Probiotic and Cancersupporting
confidence: 80%
“…For example, several Gram-positive probiotic can synthesize antimicrobial peptides, acetic, lactic, and propionic acid which reduce the intestinal pH and consequently inhibit the growth of several pathogenic Gram-negative bacteria [ 87 ]. These data were further supported by several other studies [ 88 90 ] which showed that several strains of lactobacilli have antagonistic activities against Gram-negative gastric-cancer-related Helicobacter pylori . Furthermore, another study found that some Lactobacillus strains produce lactic acid which inhibits the growth of Salmonella enterica [ 91 ].…”
Section: Probiotic and Cancersupporting
confidence: 80%
“…The yogurt was given mixed with drinking water. The scarified jerbils showed lower inflammatory score on histopathologic examination parallel to the lower H. pylori colonization rates reported among study groups .…”
Section: Helicobacter Pylori‐associated Histopathologic Featuressupporting
confidence: 68%
“…Although improvements in H. pylori‐ induced gastritis were noticed with different antibiotics used in H. pylori eradication , probiotics‐associated improvements in the histopathologic changes have particular importance due to various aspects. The effect is probably long lasting compared with the relatively short effect of antibiotics , and this may be due to its impact on the gut barriers and immunity . Once the drug is stopped, H. pylori ‐associated inflammation returns to pretreatment levels , while improvements after stoppage of probiotics were documented months later .…”
Section: What Probiotics Add To Antibiotics In Terms Of Histologic Immentioning
confidence: 99%
“…Thus, many drying techniques are employed to sustain the CFU g −1 value making it suitable for long-term storage [ 12 ].The spray drying method is found to be a most favourable technique to generate LAB granules. Spray drying yoghurt to preserve Lactobacillus and dairy starter cultures has been long investigated [ 13 ]. Lyophilised and spray-dried probiotic cultures are found to be stable with long-term storage life as compared to tray dry or other methods [ 14 ].…”
Section: Introductionmentioning
confidence: 99%